Intersectional Making of the ‘Sri Lankan Case’: the Racialization of Domestic Violence in the Swiss Police Force - Khazaei, Faten (The British journal of criminology, 2024)
This article uses an intersectional lens to ethnographically analyze police treatment of domestic violence in Switzerland. The analysis suggests three interlinked explanatory factors to understand the differential treatment of domestic violence for white Swiss/European nationals on the one hand, and racialized non-European migrants on the other. These factors are (1) prevailing generalized representations of the racialization of violence against women in Switzerland, (2) the police professional logic used to categorize sections of the public, and (3) the specific police institutional memory of two emblematic cases of domestic violence involving families of Sri Lankan nationality. The article discusses the implications of this differential treatment not only for racialized non-Europeans but also for Swiss and white European women subjected to domestic violence.